2018
DOI: 10.5897/jahr2017.0425
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and predictors of cluster of differentiation 4 (CD4) cell count recovery among cohorts of human immunodeficiency virus (HIV)-infected patients on antiretroviral therapy in Hawassa University Referral Hospital

Abstract: Cluster of differentiation 4 (CD 4 ) cell count recovery is used in determining disease progression and outcome monitoring. This study was conducted to determine the trends of CD 4 cell count recovery, and its determinants in Hawassa university referral hospital, Ethiopia. Retrospective cohort study design was employed to gather relevant data among human immunodeficiency virus (HIV) positive-patients visiting Hawassa University referral hospital. Data were collected from December 1, 2014 to May 15, 2015. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…23,24 This finding was also in line with other studies. 14,21 The median of CD4+ T-cell at baseline was 257cells/uL which was higher than a baseline median of the study done in Hawassa university referral hospital (167cells/uL). 14 The difference could be explained by the fact that our study included all participants of the age group.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…23,24 This finding was also in line with other studies. 14,21 The median of CD4+ T-cell at baseline was 257cells/uL which was higher than a baseline median of the study done in Hawassa university referral hospital (167cells/uL). 14 The difference could be explained by the fact that our study included all participants of the age group.…”
Section: Discussionmentioning
confidence: 62%
“…14,21 The median of CD4+ T-cell at baseline was 257cells/uL which was higher than a baseline median of the study done in Hawassa university referral hospital (167cells/uL). 14 The difference could be explained by the fact that our study included all participants of the age group. A high proportion of patients exhibited immunologic nonresponse (22.1%) after 12 months of treatment, a proportion similar to that observed in a study conducted in Northern Ethiopia (22.7%) 7 but higher than the study done in Hawassa, southern Ethiopia (19.3%).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, the clinical and immunological responses among patients in AIDS stages and others are mixed. Some studies have shown that recovery response is strongly related to baseline CD4 count [5,6]. Many researches have shown that patients with lower baseline CD4 are recovery worse [7][8][9].…”
Section: Introductionmentioning
confidence: 99%